Bifundamental fuzzy 2-Sphere and fuzzy killing spinors - Nastase, Horatiu [UNESP]; Papageorgakis, Constantinos (SIGMA (Symmetry, Integrability and Geometry: Methods and Application), 2010)
We review our construction of a bifundamental version of the fuzzy 2-sphere and its relation to fuzzy Killing spinors, first obtained in the context of the ABJM membrane model. This is shown to be completely equivalent to the usual (adjoint) fuzzy sphere. We discuss the mathematical details of the bifundamental fuzzy sphere and its field theory expansion in a model-independent way. We also examine how this new formulation affects the twisting of the fields, when comparing the field theory on the fuzzy sphere background with the compactification of the 'deconstructed' (higher dimensional) field theory.
Keywords: Field theory; Fuzzy sphere; Noncommutative geometry